Serial MRI in listeria mesenrhombencephalitis: a case report. Issue 5 (November 1995) - Lever, N; Haas, L
Abstract : Listeria mesenrhombencephalitis is a rare disorder, especially in the non-immunocompromised host. The predilection for brain stem involvement is unexplained. The anatomical correlation of brain stem signs with serial MRI over three months is shown in a 64 year old white man. The pathological lesions seemed to be a combination of micro-abscesses and associated oedema.